An In-depth Look at the Challenges in Managing Portrait Islamic Boarding Schools and Future Prospects - Kharisman Etika Halza; Hilalludin Hilalludin; Adi Haironi (Asosiasi Riset Ilmu Pendidkan Agama dan Filsafat Indonesia, 2024)
This research aims to compare education in Salafi and modern Islamic boarding schools in Indonesia. Salafi Islamic boarding schools tend to maintain the teaching of the Yellow Book and traditional methods, while modern Islamic boarding schools integrate religious education with general education and technology. The library study method is used to collect and analyze data from various sources such as books, journals and related articles. The research results show that Salafi Islamic boarding schools remain focused on teaching the classical books of the Islamic religion without adopting a modern curriculum, while modern Islamic boarding schools offer more integrated education by combining religious and general curricula, as well as modern technology. These differences are reflected in the teaching methods, curriculum structures, and leadership approaches in both types of Islamic boarding schools, which is important for understanding their contribution to developing the character and knowledge of young people and supporting the formation of more inclusive education policies in Indonesia.